The Analysis Validity Of Self-Determination Instrument In Adolescents Using Rasch Model - Suryana, Dodi; Yuliani, Rahmawati; Ali, Enjang Yusup (Universitas Ahmad Dahlan, 2023)
This study was conducted to analyse the validity of the self determination instrument. The study used a quantitative approach with a cross-sectional survey design with a convenience sample technique of 102 people, consisting of 45 men and 57 women, in junior high schools in West Java, Indonesia. The self-determination instrument was elaborated from Ryan and Deci's Theory, with 17 items and 6 levels of answer choices. Data were analysed using the Rasch Model with the help of Winstep software version 3.73. Analysis of self-determination instrument results through the Rasch model based on aspects of unidimensionality, item analysis (item difficulty level and item suitability level), diagnostic rating scale and instrument analysis. The results of the reliability value of 0.91 so that it can be used as a consideration of measuring instruments to measure self-determination abilities in junior high school students, and the Guidance and Counselling process can be implemented in the need assessment step.